2015
DOI: 10.1002/jms.3704
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating collision induced dissociation products and reaction mechanisms of protonated uracil by coupling chemical dynamics simulations with tandem mass spectrometry experiments

Abstract: In this study we have coupled mixed quantum-classical (quantum mechanics/molecular mechanics) direct chemical dynamics simulations with electrospray ionization/tandem mass spectrometry experiments in order to achieve a deeper understanding of the fragmentation mechanisms occurring during the collision induced dissociation of gaseous protonated uracil. Using this approach, we were able to successfully characterize the fragmentation pathways corresponding to ammonia loss (m/z 96), water loss (m/z 95) and cyanic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 54 publications
3
51
0
Order By: Relevance
“…In order to confirm the above scenario, simulations and/or evaporation rates calculation would have to be conducted to describe the fragmentation channels in details. Such molecular dynamics simulations have already been performed by Spezia and coworkers to understand the collisional induced dissociation of various organic molecules [9,10,43,44]. Although in the present case the initial position of the excess proton appears as a key parameter to explain the evaporation of neutral uracil, such simulations could be additionally conducted to provide a clearer picture on the various evaporation pathways.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In order to confirm the above scenario, simulations and/or evaporation rates calculation would have to be conducted to describe the fragmentation channels in details. Such molecular dynamics simulations have already been performed by Spezia and coworkers to understand the collisional induced dissociation of various organic molecules [9,10,43,44]. Although in the present case the initial position of the excess proton appears as a key parameter to explain the evaporation of neutral uracil, such simulations could be additionally conducted to provide a clearer picture on the various evaporation pathways.…”
Section: Discussionmentioning
confidence: 93%
“…to understand reactivity and provide access to structural information [7]. Fragmentation of the bare protonated uracil molecule has already been performed under CID with tandem mass spectrometry [8,9,10,11,12], but there are only few studies available concerning the effect of hydration on such process. Infrared photodissociation spectroscopy of singly hydrated protonated uracil [13] shows that the most stable tautomeric form of the neutral uracil (di-keto) differs from the most stable one for bare protonated uracil (keto-enol).…”
Section: Studying Fragmentation Of Biomolecules Through Collision Indmentioning
confidence: 99%
“…Recently, we have shown that semi-empirical methods can be an alternative way to qualitatively understand reaction dynamics, mainly in the field of unimolecular dissociation, 21,22,23,24,25,26 and also in the study of ion-molecule collision, where we found that MSINDO semi-empirical Hamiltonian gives results qualitatively in agreement with MP2. 19 Here we first tested a larger variety of semi-empirical Hamiltonians on the reaction responsible to formamide formation for which we have benchmark MP2 results and thus used the one performing better to study the ion-molecule collisions of reactions 1 and 2.…”
Section: Introductionmentioning
confidence: 78%
“…[12] Finally, it is also worth noting that activation of the ions by sequential absorption of IRMPD photons may promote the isomerization of the enolic forms prior to dissociation. Our recent chemical dynamic simulation study of the collision induced dissociation of protonated uracil [25] demonstrated that the enolic form of protonated uracil, strictly similar to 1MeU2_ha and 6-MeU2_ha, is totally unreactive upon CID activation, and that interconversion towards more reactive protonated forms has to take place to explain the CID fragments observed experimentally. Figure 4 compares the experimental IRMPD spectrum of protonated 3-Me-uracil (Figure 4a) to the computed vibrational spectrum of the two most stable optimized keto forms, and of the 3MeU2_ha structure (Figure 4b-d).…”
Section: Irmpd Spectra Of Protonated 1-me-and 6-meuracilmentioning
confidence: 99%
“…Among those, Infrared Multiple Photon Dissociation spectroscopy (IRMPD) of mass-selected ions, is now established as a very powerful approach to probe the structure of gaseous ions of moderate size, [7][8][9][10], and different groups have used IRMPD spectroscopy to study the structure and tautomerization of protonated DNA and RNA building blocks generated by electrospray [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. In our continuing effort to study the structure and unimolecular reactivity of gaseous nucleobases, either protonated [11][12][13]25,26] or complexed to metals [27][28][29][30][31][32], the present paper reports the IRMPD study in the fingerprint region between 1000 and 2000 cm -1 of three protonated methyluracils, namely 1-Me, 3-Me and 6-Me-uracil (Scheme 1), generated by electrospray ionization and trapped in a quadrupole ion trap. The study is complemented by DFT and ab-initio electronic structure calculations that provide information regarding the relative stability of the different conformers and their vibrational modes.…”
Section: Introductionmentioning
confidence: 99%